Mental Imagery Skills in Competitive Young Athletes and Non-athletes - Di Corrado, Donatella; Guarnera, Maria; Guerrera, Claudia Savia; Maldonato, Nelson Mauro; Di Nuovo, Santo; Castellano, Sabrina; Coco, Marinella (Frontiers in Psychology, 2020)
Mental imagery is a fully immersive multi-sensory procedure that associates as numerous senses to create a mental image and process it without the presence of external stimuli. In the sport situation, imagery has been designated as the state in which people imagine themselves while effecting abilities to deal with the forthcoming duty or improve performance. Methodical analyses have revealed that imagery increases performance in motor tasks. This study aims at observing not the vividness of image but the cognitive abilities useful for the inspection, maintenance, generation, and manipulation of dissimilar classes of images, investigating modifications in mental imagery skills in competitive athletes and non-athletes. Participants were competitive athletes (n = 48) and non-athletes (n = 48) between the ages of 8 and 13 years (Mage = 10.50, SD = 1.73). The athletes had a minimum of 5 years of training skill in the sport. They completed the Mental Imagery Test (MIT). Competitive athletes showed higher scores on mental imagery skills than non-athletes. The study contributed to increase the exploration in the definite area of mental imagery, supplying an added support for the pluridimensional nature of mental imagery and for its practicality in motor and sport sciences.